The economic contribution factors of stokvels in the local economy of eThekwini Municipality - Bophela, Mduduzi Justice Kennedy; Khumalo, Njabulo (Technium Social Sciences Journal, 2022)
The absence marginalisation and lack of recognition of the role of stokvels in the official economic plans and policies of the municipality was therefore the problem that this paper sought to explore. Simple random method was adopted on 395 stokvel group’s members who were administered with a questionnaire and the purposive sampling method on 6 MC members of eThekwini Municipality that participated in the interviews. The qualitative data was analysed using N-VIVO (version 11.0). The quantitative data was analysed using inferential and descriptive statistics. Money saving & investment, job creation and promoting business opportunities are the most prevalent of the economic contribution factors of stokvels. EM needs to pioneer the amendment of the current policy inclusive of the informal economy.